Running Dogs in Capitalist Japan: Review of Aaron Herald Skabelund, Empire of Dogs: Canines, Japan, and the Making of the Modern Imperial World - Gordon, Joan (Humanimalia, 2013)
Aaron Herald Skabelund. Empire of Dogs: Canines, Japan, and the Making of the Modern Imperial World. Ithaca, NY: Cornell UP, 2011. xv + 267 pp. $39.95 hc.